THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT PT. MEARES SOPUTAN MINING - Rondonuwu, Cecillia (Universitas Sam Ratulangi, 2013)
Along with the complexity that getting highest and the pressure of the competition that faced by the company, the Corporate Governance become one of the important topic that discuss in global business. Many of corporate scandal become one issue that attract the attention of the international community to give more concern in Corporate Governance. The research objective of this research is to examine the implementation of Good Corporate Governance at PT MSM as the international mining company. Theory related research is good corporate governance. The population is employees at PT. Meares Soputan Mining with sample of 8 informants who know about the implementation of good corporate governance in PT. Meares Soputan Mining. Researcher used qualitative methods to explain the result of research. Result and conclusion is PT. Meares Soputan Mining already implementing the five principals of good corporate governance that are transparency, accountability, responsibility, independency, and fairness in every section in their company. But the company still need the improvement especially in the responsibility and independency, to make the good corporate governance in company more effective and efficient so the company can reduce the problem and reach the goal of company. Keywords: good corporate governance